The conserved role of protein restriction in aging and disease. Issue 1 (January 2016) - Mirzaei, Hamed; Raynes, Rachel; Longo, Valter D.
Abstract : Purpose of review: Dietary interventions are effective strategies for preventing disease and promoting health span. Many of the effects of dietary restriction are linked to amino acid and protein levels and their regulation of nutrient-signaling pathways. Thus, protein restriction is a promising therapeutic strategy for preventing aging-related diseases and extending life span. Recent findings: Studies in yeast and flies have shown that amino acid restriction promotes longevity and protection. In rodents, protein restriction extends life span and alleviates detrimental aging phenotypes. Finally, clinical trials in middle-aged adults have demonstrated the role of a protein-restricted diet in promoting health span. Interestingly, the population over the age of 65 may not benefit from severe protein restriction potentially because of the increased physiological decline that leads to decreased amino acid absorption and altered protein synthesis. Summary: Protein restriction can have profound effects on health and longevity, but excessive restriction is detrimental, particularly in the very old. The investigation of the mechanisms that modulate nutrient-sensing pathways is important to understand how regulation of protein intake can optimize health span and longevity.